IMPLEMENTASI MUATAN LOKAL PENCAK SILAT UNTUK MENINGKATKAN LITERASI BUDAYA DI SDN BANJARSARI 5 - Auliya, Ananda Fatihah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the implementation of local content of pencak silat in improving student literacy at SDN Banjarsari 5. This study aims to analyze the role of local wisdom in strengthening national identity amidst the flow of globalization. In the modern era, preserving local culture is important as an effort to maintain Indonesia's cultural heritage. Through a qualitative approach with descriptive methods, data were collected through observation, interviews, and documentation of trainers, class teachers, and students. The results of the study show that pencak silat not only plays a role as a physical activity, but also becomes a means of internalizing local cultural values such as responsibility, sportsmanship, respect, and love for the country. Learning takes place contextually with the support of careful planning, collaboration between teachers and trainers, and the use of culture-based learning media. The implementation of this local content has proven effective in shaping character and strengthening student identity, as well as encouraging their active participation in meaningful learning. Recommendations from this study emphasize the importance of teacher training, provision of facilities, and strengthening policies so that culture-based education can be sustainable and widespread.